Using eggshells as a sustainable substitute for floor tile material - Mohd Nizam, Muhammad Azam Danish; Adam Zizaki, Muhammad Nabil; Manah, Mohammad Azwar Dol; Hassan, Nurul Arisya Syazwani (2024)
This paper explores the potential of using eggshells as a substitute for floor tile material, aligning with the principles of sustainable design and waste reduction. The concept involves combining eggshells with a binding agent or resin to create a composite material with the necessary structural integrity. The feasibility of this approach is considered from various aspects, including material properties, processing, composite material development, aesthetics and design, environmental impact, and potential benefits. The study highlights the challenges associated with collecting and processing large quantities of eggshells, ensuring the material performance meets required standards, and gaining market acceptance. Implementation steps are proposed, including research and development, prototype creation, testing and certification, scaling up, and market introduction. The study concludes that while the concept is not yet mainstream, it holds potential as an innovative and sustainable solution that can contribute to more sustainable building practices and waste reduction efforts.